DESIGN OF RETAINING WALL USING ALTERNATIVE GABION AND RETAINING WALLS OF CANTILEVER TYPE ON SLOPE OPEN SPACE GREEN JL. KINIBALU BANJARBARU - Adelina Melati Sukma (CERUCUK, 2021)
On the construction of green open space Jl. Kinibalu Banjarbaru There is a 6 meters tall slope beneath which the river is lined up during the rainy season and makes the slope exposed by water plus the absence of load or traffic on it make the pore figures on the land is large. Therefore, for protection reason, there is a soil alignment in the construction of soil retaining walls. The planned ground retaining wall type is cantilever and gabion. The stability analysis of the ground retaining walls is done manually and with the help of the Geoslope/W 2018 software. The value of the stability of the style against the bolsters, sliding, and carrying capacity of the soil using manual calculations for cantilever type and Netlon qualifies SNI 8460:2017. And for the overall stability calculation using Geoslope/W 2018 software obtained safety factor (SF) > 1.5. From the analysis, the design of planning can be used because it is safe against the dangers of avalanche.